Evaluating liaison and diversion schemes: an analysis of health, criminal and economic data. Issue 4 (4th July 2017) - Earl, Forbes; Cocksedge, Karen; Morgan, John; Bolt, Mark
Abstract: Introduction : Liaison and Diversion (L&D) currently serves 50% of the population of England. L&D relies on modified working practices with key delivery partners, especially the police. Service evaluation data is thus presented from both police and health services.Method : A before and after intervention review of 3 months of operational data of L&D in Cornwall focusing on health, criminal and economic outcomes.Results : After L&D intervention individuals' contact with the police as either victim or perpetrator reduced significantly.Implications : Preliminary findings suggest that L&D enabled reduced use of police and criminal justice resources. National reporting procedures may be unable to demonstrate the multi-agency impact if criminal justice data are not considered within the outcome data-set. Recommendations echo international observations that specifying outcome measures and the consistent definition of L&D services would enable generalisation of findings.